PENGEMBANGAN MIKROEMULSI DARI EKSTRAK ETANOL 96% KULIT BATANG BALIK ANGIN (Alphitonia incana (Roxb.) Teijsm & Binn. Ex Kurz) - Wahyudin Bin Jamaludin; Muhammad Hidayattullah; Muammaroh; Fitriyanti; Marlia Fatwa (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2025)
The 96% ethanol extract of Balik angin stem bark contains secondary metabolite compounds that have potential antioxidant activity with a value of 37.00 ± 1.46µg/ml (bpj), the potential for use can be maximized in microemulsion preparations. In microemulsions, one of the ingredients that can affect the stability of the microemulsion is a cosurfactant which can affect the globule size and polydispersity index. Microemulsions were formulated by varying the type and concentration of cosurfactants to determine the optimal formula based on the test parameters of physical characteristics and stability of the preparation. The method used in this research is experimental and in the manufacture of microemulsions, namely the spontaneous emulsification method. The test results show that all formulas in the organoleptic test are clear except F1, the Tyndall test can transmit light, the pH value is 5.4 -5.6, the microemulsion type is M/A, the specific gravity is 1.038-1.064, the viscosity value is less than 200 cPs and the percent transmittance obtained ranges from 90-97%. The globule size test of F2 to F6 (55.03-1045) and the polydispersity index test of F2 to F6 (0.277-0.827), but the results were not detected in F1. The results of statistical tests on pH and specific gravity tests obtained p-value (>0.05), F3 viscosity test obtained p-value (<0.05) and T% test on F1, F4, and F5 obtained p-value (<0.05) so it can be concluded that microemulsion preparations with variations in the type and concentration of cosurfactants have an influence on physical characteristics and stability, and the most optimal formula is F6.